The Effect of Promotion and E-WOM on Tourists’ Intention to Visit Denpasar: Destination Image as a Mediating Variable - Putu Surya Laksana Rahjasa; I Putu Utama; Luh Yusni Wiarti (Politeknik Pariwisata Bali, 2022)
This study aimed to investigate the effect of promotion and E-WOM on tourists’ intention to visit Denpasar and how the destination image as a mediating variable to increase the intention. Data were collected using a questionnaire to 104 respondents of foreign tourists who were in the province of Bali except for tourists who were in the city of Denpasar. The data were analysed using the Structure Equation Model (SEM) AMOS version 23. The results showed that, destination image had a significant effect on tourists' intention to visit. Promotion had no significant effect on intention to visit. E-WOM has no significant effect on intention to visit because. However, Promotion has a significant effect on visit intention through destination image with a Sobel test value of 3.214 as well as E-WOM has a significant effect on intention to visit through destination image with a Sobel test value of 2.840. It can be concluded that promotion and E-WOM are able to create a destination image, it will increase the Visiting Intention of tourists to Denpasar City.